The KRASG12C inhibitors in lung cancer therapy - Jędrak, Maciej; Niekurzak, Karolina; Kania, Joanna; Józefiak, Maciej; Sobkiewicz, Piotr; Kania, Krzysztof (Journal of Education, Health and Sport, 2023)
Introduction: Lung cancer is characterized by the highest mortality among cancers and is the second most frequently diagnosed type of cancer in the world. Targeted therapies are a promising therapeutic option for patients with this disease, however, one of the most common and most malignant mutations (KRAS) remains a challenge. Purpose: The aim of this study is to bring closer the problem of the KRAS mutation, in particular KRASG12C, and to present the most important information about the compounds created for therapies targeted at it. For a better understanding of the issue, the study contains information about the mechanisms of both mutation and drugs, as well as the most important statistical data and research results. Materials and methods: The review was based on articles available in the PubMed database. Conclusions: Two drugs targeting KRASG12C (sotorasib and adagrasib) have proven their clinical effectiveness and represent a milestone in the development of targeted therapies for lung cancer with this mutation. However, they are not without side effects, and the emerging resistance and presence of commutations that reduce drug potency continue to challenge the scientific community. Research is underway to refine therapies using existing inhibitors as well as to develop further compounds targeting KRASG12C.